KONSEP MANAJEMEN KELAS DAN IMPLIKASINYA DALAM PEMBELAJARAN - Indriani, Novi; Hasanah, Tri Fazri (PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM, 2023)
The teacher is a manager or a planner in the classroom, the cleverness of a teacher in making plans will have an impact on learning. At this time, Indonesia is being surprised by a change in the curriculum, from the K13 curriculum to an independent curriculum. Therefore, teachers already have the full rights or freedom in teaching students and students will not be bored because students also have the freedom to learn, where both play a role in each other. The concept of good classroom management is a concept that has a good impact on learning, so that from this concept it can change to a better or advanced direction. And the research method that the author uses is with a literature study approach, which comes from book references, and others. The concept of classroom management and its implications in learning, can help students stimulate their minds, besides that it has an impact on the ease of teachers in teaching in the classroom, and has an impact on the creation of planned learning and the funds are definitely good because it has been planned and implemented properly. In addition, students must also have good cooperation by the teacher, so that the concept will have good impacts on the learning itself. The way to conceptualize class management is with Classroom Arrangement, the class environment needs to be well organized so as to allow active interaction between students and teachers, and between students. There are several principles that need to be considered by teachers in managing the physical environment of the classroom according to Loisell, namely: Visibility (Wideness of View), Accessibility (easy to achieve), Flexibility (Flexibility), Comfort, Beauty.